The Influence of Packaging and Brand Equity on Over-The-Counter Herbal Medicines in Kumasi, Ghana - Oppong, Peter Kwasi; Phiri, Maxwell A (Journal of Economics and Behavioral Studies, 2018)
In today`s competitive business environment, packaging and brand equity provide a competitive advantage to a firm which may increase and maintain its market share. However, the role of packaging in supporting the brand equity is relatively new in the over-the-counter pharmaceutical market and currently, there is a lack of empirical research to uncover its significance in this product segment. This paper seeks to investigate the impact of packaging on brand equity through the mediating effect of dimensions of brand equity in the over-the-counter drug market in Kumasi metropolis. Based on Aaker`s customer-based brand equity model, eight hypotheses were formulated and tested through structural equation modelling. Using systematic sampling, data was collected through survey questionnaires from a sample of 348 consumers who patronize in herbal medicines from herbal stores in Kumasi Metropolis. The study found that packaging significantly contributes to support brand equity of plant medicines through the mediating effect of brand awareness, brand association and brand loyalty. These results indicate that brand managers in the plant medicine industry need to consider packaging as an important brand-building tool in their marketing strategy to enhance brand equity in the over-the-counter pharmaceutical market. This will enh0ance their competitive distinctiveness in the over-the-counter market.